STUDI PENGUKURAN KESADARAN MEREK (BRAND AWARENESS) PADA PRODUK TEH BOTOL SOSRO DI BANDAR LAMPUNG (MEASUREMENT STUDY BRAND AWARENESS ON TEH BOTOL SOSRO IN BANDAR LAMPUNG) - Indah, Has (Jurnal Manajemen Magister Darmajaya, 2015)
Object of this thesis is the study of PT Sinar Sosro in Belfast, one distributor of tea in a bottle with the brand Botol Sosro. PT RAY SOSRO is a ready to drink tea in bottles of the first in Indonesia and in the world. SOSRO is the pioneer of tea ready to drink products in the packaging of the first in Indonesia. The problems studied were measuring Brand Awareness study on Teh Botol Sosro product in Bandar Lampung. Teh Botol Sosro product still perceived by most people in the region known to Bandar Lampung. Indonesian society is very fond of drinking tea, the survey result from various research institutes such as AC Nielsen, MARS and SWA, since 1999 until now, shows the level of market penetration for the tea reaches more than 95%. That means drink tea or almost have been consumed by every member of society. The method of this research is Descriptive method is to identify and analyze Brand Awarenes, which consists of Top of Mind Brand Recall, Brand Recognition and unaware of Brand on Teh Botol Sosro product in Bandar Lampung. The method used in this study were : Research Library and Field Research. The research literature is the research done by studying literature, literature and reading books related to this thesis research. Documentation, which is used to obtain daata on the number of consumers and the sales volume and others. As for Field Research is a method of field research conducted by the method of survey is to collect data from questionnaires or interview. The results of studies on Brand Awareness Measurement on Teh Botol Sosro product in Bandar Lampung, figures obtained 51.6% of the respondents surveyed. This figure could be raised again for the better when the PT Sinar Sosro can increase brand awareness held by consumers with more incentive to do the promotion again in collaboration with others, so that consumer brand awareness has increased. In this way will further enhance consumer loyalty on Teh Botol Sosro product brand that will increase corporate profits, then the direct sales of bottled tea Sosro will increase to higher than now.Keyword: Brand Awareness, Customer, Market